Clinical Outcomes Following Letrozole Treatment according to Estrogen Receptor Expression in Postmenopausal Women: LETTER Study (KBCSG-006) - Ahn, Sung Gwe; Nam, Seok Jin; Ahn, Sei Hyun; Jung, Yongsik; Park, Heung Kyu; Lee, Soo Jung; Kang, Sung Soo; Han, Wonshik; Park, Kyong Hwa; Park, Yong Lai; Lee, Jihyoun; Youn, Hyun Jo; et al. (Journal of breast cancer, 2021)
In this trial, we investigated the efficacy and safety of adjuvant letrozole for hormone receptor (HR)-positive breast cancer. Here, we report the clinical outcome in postmenopausal women with HR-positive breast cancer treated with adjuvant letrozole according to estrogen receptor (ER) expression levels. In this multi-institutional, open-label, observational study, postmenopausal patients with HR-positive breast cancer received adjuvant letrozole (2.5 mg/daily) for 5 years unless they experienced disease progression or unacceptable toxicity or withdrew their consent. The patients were stratified into the following 3 groups according to ER expression levels using a modified Allred score (AS): low, intermediate, and high (AS 3-4, 5-6, and 7-8, respectively). ER expression was centrally reviewed. The primary objective was the 5-year disease-free survival (DFS) rate. Between April 25, 2010, and February 5, 2014, 440 patients were enrolled. With a median follow-up of 62.0 months, the 5-year DFS rate in all patients was 94.2% (95% confidence interval [CI], 91.8-96.6). The 5-year DFS and recurrence-free survival (RFS) rates did not differ according to ER expression; the 5-year DFS rates were 94.3% and 94.1%in the low-to-intermediate and high expression groups, respectively ( = 0.6), and the corresponding 5-year RFS rates were 95.7% and 95.4%, respectively ( = 0.7). Furthermore, 25 patients discontinued letrozole because of drug toxicity. Treatment with adjuvant letrozole showed very favorable treatment outcomes and good tolerability among Korean postmenopausal women with ER-positive breast cancer, independent of ER expression. ClinicalTrials.gov Identifier: NCT01069211.